Improving a Measuring System According to ISO / TS 16949. (2015) - Pop, Liviu Dorin; Elod, Nagy
Abstract: One of the requirements of the standard ISO/TS 16949 is conducting statistical studies for each type of measurement system, which means using Measurement System Analysis (MSA) as a method of identifying the sources of variation in the measurement process. This paper highlights the use of MSA (Measurement Systems Analysis) in a company that manufactures automotive parts and plans to attain the ISO/TS 16949 certification. MSA method is used in order to correct a problem that occurred on the surface of an automotive part, specifically by improving the device that measures the runout of a specific product. In the study a measuring device is used, a sample of ten parts and three operators, each measuring with the same principal the same part twice. Three options are selected, compared between them and the most advantageous is chosen.